Republic of Tajikistan : 2011 Article IV Consultation, Fourth Review Under the Three-Year Arrangement Under the Extended Credit Facility, Request for Waiver of Nonobservance for Performance Criteria and Modification of Performance Criterion-Staff Report; Staff Supplements; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2011)
In recent years, the IMF has released a growing number of reports and other documents covering economic and financial developments and trends in member countries. Each report, prepared by a staff team after discussions with government officials, is published at the option of the member country.